Obesity and Complication Risk From Radical Cystectomy: Identifying a Body Mass Index Threshold. Issue 1 (11th January 2023) - McLoughlin, Louise Catherine; Kassouf, Wassim; Breau, Rodney H.; Fairey, Adrian; Agnihotram V, Ramanakumar; Salimi, Afsar; Hyndman, Eric; Drachenberg, Darrel E.; Izawa, Jonathan; Shayegan, Bobby; Lattouf, Jean-Baptiste; Lodde, Michele; et al.
Abstract : Purpose: There are conflicting reports regarding radical cystectomy complication risk from obesity subcategories, and a BMI threshold below which complication risk is notably reduced is undefined. A BMI threshold may be helpful in prehabilitation to aid patient counseling and inform weight loss strategies to potentially mitigate obesity-associated complication risk. This study aims to identify such a threshold and further investigate the association between BMI subcategories and perioperative complications from radical cystectomy. Materials and Methods: Data were extracted from the Canadian Bladder Cancer Information System, a prospective registry across 14 academic centers. Five hundred and eighty-nine patients were analyzed. Perioperative (≤90 days) complications were compared between BMI subcategories. Unconditional multivariable logistic regression and cubic spline analysis were performed to determine the association between BMI and complication risk and identify a BMI threshold. Results: Perioperative complications were reported in 51 (30%), 97 (43%), and 85 (43%) normal, overweight, and obese patients ( P = . 02). BMI was independently associated with developing any complication (OR 1.04 95% CI 1.01, 1.07). Predicted complication risk began to rise consistently above a BMI threshold of 34 kg/m 2 . Both overweight (OR 2.00 95% CI 1.26-3.17) and obese (OR 1.98 95% CI 1.24-3.18) patients had increased risk of complications compared to normal BMI patients. Conclusions: Complication risk from radical cystectomy is independently associated with BMI. Both overweight and obese patients are at increased risk compared to normal BMI patients. A BMI threshold of 34 kg/m 2 has been identified, which may inform prehabilitation treatment strategies.